The effect of inflation, profit-loss sharing loan, and capital adequacy towards performance of Indonesian Islamic banks - Luksi Visita (Diponegoro International Journal of Business, 2019)
The purpose of this study is to observe the impact of inflation, profit-loss sharing loan, and capital adequacy towards performance of Islamic banks in Indonesia. This study utilizes longitudinal study from 2010 to 2018 towards Islamic Commercial Banks and Sharia Business Units that are listed in Indonesia. Using pool-time series data, the variables studied are inflation, capital adequacy ratio (CAR), profit-loss sharing loan, and return on assets (ROA). The result shows that only inflation has no significant effect on performance. Capital adequacy affects positively significant, while profit-loss sharing loan affects negatively significant. This study add new perspective on how macroeconomic variable influence Islamic banks’ performance in Indonesia. Additionally, this study is also distinctive because of lengthier observation period (eight years) compared to other studies in recent five years